MODEL KERJASAMA ANTAR DAERAH DALAM PERENCANAAN SISTEM TRANSPORTASI WILAYAH METROPOLITAN BANDUNG RAYA (Inter-regional Cooperation Model of Transportation System Planning in the Greater Bandung Metropolitan) - Tessa Talitha; Delik Hudalah (TATALOKA, 2014)
Decentralization policy in Indonesia gives development authority at local government level which cause fragmentation among regions. On the other hand, there are some government affairs that need to be managed jointly between several regions, so that inter-regional cooperation is necessary. Greater Bandung Metropolitan has rapid development from Bandung City to regions arround it. With the increasing of activity rate, good infrastructure planning including transportation system planning are needed. Decision making in planning implies many considerations, so that transaction cost such as information, negotiation, enforcement, and agency were involved. For the purpose of increasing public services, study of inter-regional collaboration models are needed. Based on the analysis, found that there are factors that will cause transaction costs such as unequal distribution of information, conflict of interest, actor who dominates, and lack of commitments of stakeholders. Then the results obtained that the model that appropriate to applied in Greater Bandung Metropolitan is jointly-formed authority, which is an institution consisting of representatives from each local governments and has the authority to execute policy in particular sector.